MICROBIOLOGICAL QUALITY AND SAFETY OF DIETARY SUPPLEMENTS SOLD IN SAUDIARABIA - Aljaloud# , Sulaiman O.; Ibrahim , Salam A.; Fraser , Angela M.; Song, Tammy; Shahbazi, Abolghasem (Emirates Journal of Food and Agriculture, 2013)
The global market for dietary supplements has advanced in recent years capitalizing on the growing awareness of healthy living worldwide. Supplements provide enhanced nutritional levels for daily competitive performance. However, there is a need to explore the quality of dietary supplements as there are few studies related to this area. Therefore, the objective of this study was to determine the microbiological quality of dietary supplements in the local markets of Saudi Arabia. The total bacterial count, coliform, Escherichia coli, Salmonella, and Staphylococcus aureus were included in this analysis. The 80 most popular supplements were tested in this study. Our results showed that microbial contamination was present in only nine products. The microbial level ranged from 1.69?8.43 Log CFU/mL. The higher level of total count (8.43 Log CFU/mL) and S. aureus (8.39 Log CFU/mL) were found in supplement glutamine. Amino acids, dynamisan, glucosamine sulfate, glucosaiene, creatine monohydrate, whey protein, and folate acid also showed the presence of bacterial contamination. Our findings suggested that improvements are needed in these supplements which were tested for microbiological contamination. These findings highlight the fact that a review of product safety and quality is becoming increasingly important for consumer health. This will help to ensure safe products available for today's savvy, health-conscious consumer.